Gas chromatographic-mass spectrometric investigation of n-alkanes and carboxylic acids in bottom sediments of the northern Caspian Sea - Kenzhegaliev, Akimgali; Zhumagaliev, Sagat; Kenzhegalieva, Dina; Orazbayev, Batyr (Instytut Geologii UAM, 2018)
Prior to the start of experimental oil production in the Kashagan field (northern part of the Caspian Sea), n-alkanes and carboxylic acids contained in samples obtained from bottom sediments in the area of artificial island “D” were inves- tigated by gas chromatography–mass spectrometry. Concentrations of 10 n-alkanes (composed of C 10 -C 13 , C 15 -C 20 ) and 11 carboxylic acids (composed of C 6 -C 12 , C 14 -C 16 ) were identified and measured. Concentrations of individual alkanes and carboxylic acids in bottom sediments of the various samples varied between 0.001 ÷ 0.88 μg/g and 0.001 ÷ 1.94 μg/g, respectively. Mass spectra, in particular the M+ molecular ion peak and the most intense peaks of fragment ions, are given. The present study illustrates the stability of molecular ions to electronic ionisation and the main fragment ions to the total ion current and shows that the initial fragmentation of alkanes implies radical cleavage of C 2 H 5 rather than CH 3 . All aliphatic monocarboxylic acids studied were characterised by McLafferty rearrangement leading to the formation of F 4 cation-radical with m/z 60 and F 3 cation-radical with m/z 88 in the case of ethylhexanoic acid. The formation of oxonium ions presents another important aspect of acid fragmentation. Using mass numbers of oxonium ions and rearrangement ions allows determination of the substitution character in α- and β- C atoms. The essence of our approach is to estimate the infiltration of hydrocarbon fluids from the enclosing formation into sea water, comprising an analysis of derivatives of organic compounds in bottom sediments. Thus, concentrations of derived organic molecules can serve as a basis for estimates of the depth at which hydrocarbon fluids leak, i.e., to serve as an auxiliary technique in the search for hydrocarbon deposits and to repair well leaks.
Keywords: Gas chromatography–mass spectrometry; carbocations; oxonium ions